2018
DOI: 10.1177/2331216518770959
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Performance on Vowel Identification and the Spectral-temporally Modulated Ripple Test in Children With Normal Hearing and With Cochlear Implants

Abstract: Children’s performance on psychoacoustic tasks improves with age, but inadequate auditory input may delay this maturation. Cochlear implant (CI) users receive a degraded auditory signal with reduced frequency resolution compared with normal, acoustic hearing; thus, immature auditory abilities may contribute to the variation among pediatric CI users’ speech recognition scores. This study investigated relationships between age-related variables, spectral resolution, and vowel identification scores in prelinguall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 72 publications
3
34
0
Order By: Relevance
“…Spectral resolution was the primary contributor to the discriminant function. HiPRESTO users obtained significantly higher (better) SMRT thresholds than the LoPRESTO users, although the SMRT thresholds of the HiPRESTO group should be interpreted with caution, given the potential for spectral distortion of SMRT stimuli with high RPO values when presented through a CI processor (DiNino and Arenberg) 11 . The function of spectral resolution to speech recognition is well established.…”
Section: Discussionmentioning
confidence: 94%
“…Spectral resolution was the primary contributor to the discriminant function. HiPRESTO users obtained significantly higher (better) SMRT thresholds than the LoPRESTO users, although the SMRT thresholds of the HiPRESTO group should be interpreted with caution, given the potential for spectral distortion of SMRT stimuli with high RPO values when presented through a CI processor (DiNino and Arenberg) 11 . The function of spectral resolution to speech recognition is well established.…”
Section: Discussionmentioning
confidence: 94%
“…Effects of age and maturation were studied previously and it has been suggested that SRD matures at 7 years of age in CI recipients (Horn et al, 2017). This is based not only on chronological age but also on CI age (DiNino and Arenberg, 2018) for congenitally deaf children. Our study sample consisted of children with progressive hearing loss who may develop normal central auditory function regardless of implantation age (Sharma and Dorman, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that this increase in performance is also correlated with chronological age at testing and might therefore be due to hearing-independent development of the children. The perception of some complex, music related sounds appears to be related to hearing age rather than chronological age (DiNino and Arenberg, 2018). In the present data, these contributions cannot be separated, since hearing age and age at testing are highly correlated in the present CI participants.…”
Section: Discussionmentioning
confidence: 99%